The MMS22L–TONSL heterodimer directly promotes RAD51‐dependent recombination upon replication stress. (26th October 2016) - Piwko, Wojciech; Mlejnkova, Lucie J; Mutreja, Karun; Ranjha, Lepakshi; Stafa, Diana; Smirnov, Alexander; Brodersen, Mia ML; Zellweger, Ralph; Sturzenegger, Andreas; Janscak, Pavel; Lopes, Massimo; Peter, Matthias; et al.
Abstract: Homologous recombination (HR) is a key pathway that repairs DNA double‐strand breaks (DSBs) and helps to restart stalled or collapsed replication forks. How HR supports replication upon genotoxic stress is not understood. Using in vivo and in vitro approaches, we show that the MMS22L–TONSL heterodimer localizes to replication forks under unperturbed conditions and its recruitment is increased during replication stress in human cells. MMS22L–TONSL associates with replication protein A (RPA)‐coated ssDNA, and the MMS22L subunit directly interacts with the strand exchange protein RAD51. MMS22L is required for proper RAD51 assembly at DNA damage sites in vivo, and HR‐mediated repair of stalled forks is abrogated in cells expressing a MMS22L mutant deficient in RAD51 interaction. Similar to the recombination mediator BRCA2, recombinant MMS22L–TONSL limits the assembly of RAD51 on dsDNA, which stimulates RAD51‐ssDNA nucleoprotein filament formation and RAD51‐dependent strand exchange activity in vitro . Thus, by specifically regulating RAD51 activity at uncoupled replication forks, MMS22L–TONSL stabilizes perturbed replication forks by promoting replication fork reversal and stimulating their HR‐mediated restart in vivo . Synopsis: MMS22L–TONSL is implicated in homologous recombination, replication fork recovery, and as reader of replication‐dependent histone marks. New results show how this complex mediates recombination at stalled forks and exemplifies how recombination can protect replication under stress. MMS22L–TONSL is recruited to sites of replication fork stalling. MMS22L–TONSL interacts with RPA‐coated ssDNA filaments and the RAD51 recombinase. MMS22L–TONSL promotes DNA strand exchange by RAD51. MMS22L–TONSL promotes replication fork reversal. MMS22L–TONSL activity helps in stabilizing and restarting perturbed replication forks upon stress. Abstract : RAD51‐mediated DNA strand exchange at stalled replication forks requires RPA‐dependent fork recruitment of MMS22L–TONSL, explaining how this homologous recombination mediator facilitates fork restart.